The Impact of EFL Teachers’ Assessment Literacy on Their Assessment Efficiency in Classroom - Mostafa Rahimi Rad (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
Teachers in general and language teachers in particular are expected to assess various aspects of their teaching and learning. To achieve this, they are believed to familiar with different dimensions of assessment in general and classroom assessment in particular. Language teaching and assessment are two interrelated notions that affect each other to a great extent. Undoubtedly, language assessment is one of the most significant and complicated activities in the field of language teaching. The present study investigated assessment related perception and practices of Iranian EFL teachers. As assessment literacy questionnaire was distributed to 30 Iranian EFL teachers who were selected from two branches of private language institute, three teachers with high assessment literacy knowledge and three teachers with relatively low assessment literacy based on result of assessment literacy questionnaire were interviewed. The result of both qualitative and quantitative data indicated that EFL teachers` assessment literacy has meaningful and significant impact on Assessment efficiency in classroom. Teachers with high assessment literacy have a structured lesson plan and also know their learners` strengths and weaknesses clearly. This study suggest language policy makers to motivate language teachers to be assessment literate.